Oral Presentation No. 126 NOACs safety and efficacy in Adult Congenital Heart Disease. (21st October 2022) - Pinto, Ricardo Jorge Reis Alves; Carvalho, Miguel Martins; Proença, Tânia; Costa, Catarina; Amador, Ana Filipa; Calvão, João; Marques, Catarina; Cabrita, André; Santos, Luís; Oliveira, Cátia; Pinho, Ana; Cruz, Cristina; et al.
Abstract: Introduction: Adult Congenital Heart Disease(ACHD) patients are an increasing population with known high risk for thromboembolic events.Validated scores are uncertain in this population. Although apparently safe, data is scarce about the use of NOAC. Purpose: To evaluate all patients on-NOAC followed in an ACHD outpatients clinic and observe its safety and efficacy during a median follow-up of 34 months (IQR 7–60 months). Major bleeding was defined according to types 3 to 5 in BARC scale. Adverse event was defined as ≥ 1 of the follows: death, stroke, myocardial infarction, systemic embolism or major bleeding. Results: A total of 65 patients were included, with a mean age of 52 ± 14 year-old, 66% female. Most frequent ACHD were atrial septal defect (22%) and tetralogy of Fallot (22%), followed by atrioventricular septal defect (17%) and transposition of great arteries (9%). Most patients had preserved biventricular function, 20% presented systemic ventricle systolic dysfunction and 12% subpulmonic ventricle systolic dysfunction. Atrial fibrillation or atrial flutter (AF/AFL) were the major reasons for anticoagulation (94%); the remaining were on NOAC due to previous ischaemic stroke, intra-cardiac thrombus or deep venous thrombosis. At the time of NOAC initiation, 49% had a CHA2 DS2 -VASc score ≥ 2 (median 1, IQR 1-3) and median HAS-BLED score was 0 (IQR 0-2);43% were medicated with apixaban, 29% with rivaroxaban, 22% with edoxaban and 6% with dabigatran.During a median follow-up of 34 months, none had ischaemic complications or major bleeding and one patient died after pulmonic prothesis dysfunction surgery. Concerning time-to- adverse-event analysis, all patients kept uneventful after 2 years and more than 95% continued event-free after 8 years on-NOAC.